2008
DOI: 10.1375/twin.11.3.257
|View full text |Cite
|
Sign up to set email alerts
|

The Heritability of Life Events: An Adolescent Twin and Adoption Study

Abstract: Although life events are often conceptualized as reflecting exogenous risk factors for psychopathology, twin studies have suggested they are heritable. We undertook a mixed twin/adoption study to further explore genetic and environmental contributions to individual differences in the experience of life events. Specifically, a sample of 618 pairs of like-sex adolescent twins, 244 pairs of like-sex adopted adolescent and young adult siblings, and 128 pairs of like-sex biological siblings completed a life events … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
70
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(84 citation statements)
references
References 47 publications
13
70
1
Order By: Relevance
“…This has long been recognized within HPP (Buss 1987;Saudino et al 1997), and is increasingly recognized in BE (see Dingemanse et al 2010). Researchers have also shown that major life events in humans show substantial heritability (Bemmels et al 2008), suggesting that influences of personality variables on situational experience are ubiquitous.…”
Section: Outstanding Issues With Human Personality Psychologymentioning
confidence: 91%
“…This has long been recognized within HPP (Buss 1987;Saudino et al 1997), and is increasingly recognized in BE (see Dingemanse et al 2010). Researchers have also shown that major life events in humans show substantial heritability (Bemmels et al 2008), suggesting that influences of personality variables on situational experience are ubiquitous.…”
Section: Outstanding Issues With Human Personality Psychologymentioning
confidence: 91%
“…First, previous studies have shown that environmental and genetic factors contribute differently to the variance of dependent and independent life events. In particular, dependent life events are explained by genetic factors for the most part, whereas shared and unshared environmental factors are a larger contributor to the variance in independent life events (Bemmels et al, 2008). Second, men and women are distressed by distinctly different types of adverse events.…”
Section: Assessment Of Stressful Life Eventsmentioning
confidence: 99%
“…Researchers have distinguished independent and dependent life events (Bemmels et al, 2008). Some shocks, such as the death of a spouse or other close relative are independent and outside of any one person's control.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The list of dependent variables of social science interest for which genetic effects or gene-environment interactions have been reported is growing daily: from the frequency of life events (Bemmels et al 2008) to economic decision making (Zhong et al 2009) and the preference for coffee (Vink et al 2009). Particularly interesting are genetic variations that correlate with numerous dependent behavioral variables.…”
Section: Biosocial Data For Social Sciences Applicationsmentioning
confidence: 99%